NCLB and Its Wake: Bad News for Democracy. Issue 6 (June 2015) - Meens, David E.; Howe, Kenneth R.
Background: Local control has historically been a prominent principle in education policy-making and governance. Culminating with the passage of No Child Left Behind (NCLB), however, the politics of education have been nationalized to an unprecedented degree, and local control has all but disappeared as a principle framing education policymaking. During the same period, policies imposed upon locales by state and federal governments have shifted from an emphasis on equity to accountability. Purpose: This paper examines what the eclipse of local control through NCLB and related policies means for democracy. Research Design: Drawing upon contemporary normative democratic theory, we distinguish two dimensions of democracy that are at issue—democratic policymaking and democratic education—and conclude that the effect of NCLB has been to frustrate democracy along both of these dimensions. Findings: In terms of democratic policymaking, we argue that NCLB oversteps the boundaries that may be legitimately imposed upon local participation in policymaking on the basis of democratic principles. In terms of democratic education, we show how NCLB undermines both the content and the context of schooling likely to inculcate the skills, knowledge, and dispositions required for meaningful participation in democratic politics. Conclusions: Based upon this analysis, we offer a set of guidelines to aid in the assessment of future federal education policy vis a vis democracy. First, reform efforts should embrace a participatory model for engaging local communities. Second, curriculum standards adopted by states and locales should include a conscious and substantive focus on developing the deliberative skill and dispositions required of democratic citizenship. Third, efforts must be made to keep individuals and organizations that receive public funds accountable to the public through democratic procedures. Fourth, reform efforts must seek ways to more adequately and equitably finance schools. Fifth, the goal of better integrating schools across important categories of social difference should be revitalized in order to help ensure access to equal educational opportunities and the diverse context of learning that all students need for the inculcation of democratic character.